2021
DOI: 10.3390/jcm10245877
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Procedural Right Ventricular Longitudinal Strain and Post-Procedural Tricuspid Regurgitation Predict Mortality in Patients Undergoing Transcatheter Aortic Valve Implantation (TAVI)

Abstract: Background: Right ventricular (RV) dysfunction has been linked to worse outcomes in patients undergoing TAVI. Assessment of RV function is challenging due to its complex morphology. RV longitudinal strain (LS) assessed by speckle-tracking echocardiography (STE) is a novel measure that may overcome most of the limitations of conventional echocardiographic parameters of RV function. The aim of current study was to assess the prognostic value of RV LS in patients undergoing TAVI and to assess echocardiographic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The present data indicate that RVGLS, but not LVGLS, is an independent predictor of mortality in patients with severe AS undergoing TAVI. Previous studies observed that preinterventional RV strain plays a role in predicting outcomes in such patients (19,23,32). Those studies focused on RV strain without including LV deformation and exhibited a relatively short follow-up (23,32) or small study population (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present data indicate that RVGLS, but not LVGLS, is an independent predictor of mortality in patients with severe AS undergoing TAVI. Previous studies observed that preinterventional RV strain plays a role in predicting outcomes in such patients (19,23,32). Those studies focused on RV strain without including LV deformation and exhibited a relatively short follow-up (23,32) or small study population (19).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies observed that preinterventional RV strain plays a role in predicting outcomes in such patients (19,23,32). Those studies focused on RV strain without including LV deformation and exhibited a relatively short follow-up (23,32) or small study population (19). To the best of our knowledge, the role of RVGLS vs. LVGLS has not been investigated by STE for predicting outcomes of patients with severe AS undergoing TAVI.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting results have been reported with respect to RVLS association with mortality after TAVR. Omran et al ( 19 ) reported that pre-procedural RVLS significantly predicted long-term all-cause mortality in patients undergoing TAVR; Medvedofsky et al ( 12 ) and Vizzardi et al ( 21 ) also reported a significant association with mortality after TAVR. However, Koschutnik et al ( 20 ) reported no echocardiographic measure, including RVLS was significantly associated with outcome.…”
Section: Discussionmentioning
confidence: 99%